Diagnostic Efficacy of Liquid-Based Cytology in Endoscopic Ultrasound–Guided Fine Needle Aspiration for Pancreatic Mass Lesions During the Learning Curve: A Retrospective Study. Issue 5 (May 2019) - Mitoro, Akira; Nishikawa, Takeshi; Yoshida, Motoyuki; Sawai, Masayoshi; Okura, Yasushi; Kitagawa, Koh; Seki, Kenichiro; Furukawa, Masanori; Ozutsumi, Takahiro; Takeuchi, Mao; Morita, Kohei; Ohbayashi, Chiho; et al.
Abstract : Objectives: The diagnostic yield of endoscopic ultrasound–guided fine needle aspiration (EUS-FNA) cytology widely varies depending on the treatment method used. Liquid-based cytology (LBC) has gained popularity in the gynecological field because of its efficacy in collection of target cells and simplicity in the manipulation of specimens. Since the introduction of EUS-FNA at our institution, we have used LBC for the diagnosis of pancreatic mass lesions. This study aims to investigate the diagnostic efficacy of EUS-FNA with LBC in patients with pancreatic mass lesions during the learning curve for EUS-FNA. Methods: In this study, we retrospectively enrolled 222 patients with pancreatic mass lesions who were diagnosed using EUS-FNA with LBC between 2011 and 2016. The diagnostic yields for EUS-FNA with LBC for pancreatic mass lesions were evaluated. Results: The diagnostic sensitivity, specificity, and accuracy for malignancy were found to be 93.9%, 95.1%, and 94.1%, respectively. Conclusions: This study suggests that EUS-FNA with LBC for specimens provides good diagnostic efficacy in patients with pancreatic mass lesions even during the learning curve for EUS-FNA.